(untitled) (Lapai Journal of Economics, 2020)
This study analysed the micro economic effect of panic buying on individual savings arising from the lockdown experienced due to the coronavirus pandemic in Niger State. The study used a total sample of 384 individuals and applied a two-stage least square regression analysis using perception, price deferential and expenditure on individual savings. Finding shows that perception, price deferential and expenditure negatively affects individual savings. However, only expenses on groceries and household goods tend to contribute to household expenditure in the endogenous model. The study therefore recommends authorities interplay in the market mechanism especially by maintaining a static price to avoid price fluctuation.